EKSPERIMENTASI MODEL PEMBELAJARAN PBL, JIGSAW DAN STAD TERHADAP PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI ADVERSITY QUOTIENT (AQ) SISWA - Lia Ariati; Budiyono Budiyono; Dewi Retno Sari Saputro (Journal of Mathematics and Mathematics Education, 2016)
Abstract: The aim of this research was to know the effect of the Problem Based Learning (PBL), Jigsaw, and Students Teams Achievement Divisions (STAD) to the mathematics conceptual understanding and problem solving viewed from students Adversity Quotient (AQ). The type of this research was quasi-experimental with factorial design 3x3. The population was all the students of grade XI IPS SMA/MA in Wonogiri on the second semester of 2014/2015 academic year. The sample of this research consisted of 224 students. The instruments that used to collect the data were early ability test, conceptual understanding test, problem solving test, and questionnaires Adversity Quotient of students. Data were analyzed using unbalanced two ways multivariate analysis of variance with a significance level α = 5%. The results of the research were as follows. (1)Students who were subjected to the PBL learning model have a better conceptual understanding than with the learning model of Jigsaw and STAD while students were subjected to the learning model of Jigsaw have a better conceptual understanding than with the learning model of STAD. (b) Students who were subjected to the PBL learning model have the same problem solving as students with the learning model of Jigsaw but it have better than with the learning model of STAD while students with Jigsaw learning models have the same problem solving as students with learning model of STAD (2)Students with high AQ have better conceptual understanding and problem solving than students with medium and low AQ, and the students with medium AQ were better than low AQ. (3)(a) In learning model of PBL and Jigsaw, students with high AQ have the same conceptual understanding as medium AQ but better than low AQ, and students with medium AQ have a better conceptual understanding than low AQ while in learning model of STAD, students with high AQ have a better conceptual understanding than students with medium and low AQ, and the students with medium AQ were better than low AQ. (b) In learning model of PBL, Jigsaw and STAD, students who have high AQ have better problem solving than students who have students with medium and low AQ, and students with medium AQ have a better problem solving than students with low AQ. (4)(a) For high and low AQ, students were subjected to the PBL learning model have the same conceptual understanding as students who were subjected to the learning model of Jigsaw and STAD while for medium AQ, students who were subjected to the learning model of PBL have the same conceptual understanding as students who were subjected to the learning model Jigsaw but better than STAD and students who were subjected to the learning model of Jigsaw have a better conceptual understanding than students who were subjected to the learning model of STAD. (b) In each AQ, students with the PBL learning model have the same problem solving as students with Jigsaw learning model but better than STAD learning model, and students with Jigsaw learning model have a better problem solving than students of  STAD learning model.Keywords : PBL, Jigsaw, STAD, AQ, conceptual understanding, problem solving.